2013
DOI: 10.1039/c3dt51428e
|View full text |Cite
|
Sign up to set email alerts
|

Ring contraction of six-membered metallabenzynes to five-membered metal–carbene complexes: a comparison with organic analogues

Abstract: The ring contraction of six-membered metallabenzynes to five-membered metal-carbene complexes in comparison with the corresponding rearrangement of benzyne to cyclopentadienylidene carbene have been studied by computational quantum mechanical calculations. The rearrangement of benzyne to a cyclopentadienylidene carbene is endothermic by 27.8 kcal mol(-1). The instability of the cyclopentadienylidene carbene is attributed to the electron deficient singlet carbene carbon atom. However, the isolobal replacement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…Rearrangement is particularly favored for metallabenzynes of first-and secondrow transitionm etals, which may make isolation of compoundso ft his type particularly challenging. [155] Heterometallabenzenes An umber of heterometallabenzenes, where aC Hu nit in ah eterobenzene has been formally replaced by at ransition metal and its ancillaryl igands, have been reported over the past few decades. While other isomersa re theoretically possible, examples almost exclusively involveadirect metal-heteroatom bond.…”
Section: Metallabenzynesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rearrangement is particularly favored for metallabenzynes of first-and secondrow transitionm etals, which may make isolation of compoundso ft his type particularly challenging. [155] Heterometallabenzenes An umber of heterometallabenzenes, where aC Hu nit in ah eterobenzene has been formally replaced by at ransition metal and its ancillaryl igands, have been reported over the past few decades. While other isomersa re theoretically possible, examples almost exclusively involveadirect metal-heteroatom bond.…”
Section: Metallabenzynesmentioning
confidence: 99%
“…DFT calculations suggest that carbene formation is a low‐energy decomposition route for metallabenzynes, and the thermodynamic favorability is influenced by the steric properties of the ligands and the substituents. Rearrangement is particularly favored for metallabenzynes of first‐ and second‐row transition metals, which may make isolation of compounds of this type particularly challenging …”
Section: Metallabenzynesmentioning
confidence: 99%
“…Traditionally, the strength of transition metal–carbon bonds decreases with the ascending of a column in the periodic table ( 15 ), which results in relative lability of the first- and second-row organometallic compounds in comparison with their third-row analogs ( 16 , 17 ). In particular, cyclic metal carbyne complexes with first- and second-row transition metals are considerably less stable than their third-row counterparts both thermodynamically and kinetically, as demonstrated by computational analysis ( 18 , 19 ). Thus, intrinsic instability of the non–third-row transition metal carbynes is responsible for their absence, which greatly restrained their synthesis and further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…The most likely reaction pathway has been proposedt op roceedv ia the initial migratory insertion reactiono ft he osmabenzyne complex 57 to ac arbene intermediate, af ollowing migratory insertion of metal carbene to OsÀCl bonds, and final transformation to chlorocyclopentadienyl complex 58.D FT calculations suggested that the p-acceptingl igands, such as carbonyl group and acetonitrile, could facilitate the migratory insertion reactions of osmabenzynest o form the corresponding cyclopentadienyl complexes.T he metal effect on this migratory insertionreactions has also been studied computationally. [37] The calculation results show that the metallabenzynes with lighter metal centers are easier to transform to the corresponding cyclopentadienyl complexes for both thermodynamic and kinetic rea.…”
Section: Migratory Insertion Reactionsmentioning
confidence: 95%
“…DFT calculations suggested that the π‐accepting ligands, such as carbonyl group and acetonitrile, could facilitate the migratory insertion reactions of osmabenzynes to form the corresponding cyclopentadienyl complexes. The metal effect on this migratory insertion reactions has also been studied computationally . The calculation results show that the metallabenzynes with lighter metal centers are easier to transform to the corresponding cyclopentadienyl complexes for both thermodynamic and kinetic rea.…”
Section: Migratory Insertion Reactionsmentioning
confidence: 99%